2014
DOI: 10.1371/journal.pone.0104116
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Anal Dysplasia in an HIV-Infected Clinical Care Cohort: Estimates Using Multi-State Markov Modeling

Abstract: Objectives(1) To model the natural history of anal neoplasia in HIV-infected patients using a 3-state Markov model of anal cancer pathogenesis, adjusting for cytology misclassification; and (2) to estimate the effects of selected time-varying covariates on transition probabilities.DesignA retrospective cytology-based inception screening cohort of HIV-infected adults was analyzed using a 3-state Markov model of clinical pathogenesis of anal neoplasia.MethodsLongitudinally ascertained cytology categories were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 54 publications
(53 reference statements)
2
27
0
Order By: Relevance
“…In accord with previously published papers CD4 + cell nadir and recent CD4 + cell count were not associated with higher dysplasia (Table ) . On the other hand, two recent studies showed a protective effect of ART against high risk AIN . Nevertheless, these incongruent findings highlight the importance of routine screening and diagnostic also for HIV‐positive patients who receive optimal therapy and have good immune cell status.…”
Section: Discussionsupporting
confidence: 89%
“…In accord with previously published papers CD4 + cell nadir and recent CD4 + cell count were not associated with higher dysplasia (Table ) . On the other hand, two recent studies showed a protective effect of ART against high risk AIN . Nevertheless, these incongruent findings highlight the importance of routine screening and diagnostic also for HIV‐positive patients who receive optimal therapy and have good immune cell status.…”
Section: Discussionsupporting
confidence: 89%
“…711 A nonstatistically significant trend was found for individuals with suppressed viral load on the single variable analysis (Table 3) to have a reduced odds of having HSIL (OR, 0.54; 95% CI, 0.26–1.11; P = 0.094), which would have been consistent with prior data. 12 Additionally, cigarette smoking was found to have a nonstatistically significant trend toward increased odds of developing HSIL in both the single variable and multivariable logistic regression analysis of the data (Tables 3 and 4), and this was consistent with prior literature. 7 …”
Section: Discussionsupporting
confidence: 86%
“…The role of HPV testing in anal cytology remains to be elucidated and was not analyzed in this study. There is a high likelihood of regression of HGSIL at two-year follow-up with only about 1-2% progressing to anal cancer [15]. Patients on antiretroviral therapy, who had low HIV viral load, and a CD4 count greater than or equal to 350/mm 3 were not as likely to progress from lower grade lesions to higher grade lesions [15].…”
Section: Discussionmentioning
confidence: 99%
“…There is a high likelihood of regression of HGSIL at two-year follow-up with only about 1-2% progressing to anal cancer [15]. Patients on antiretroviral therapy, who had low HIV viral load, and a CD4 count greater than or equal to 350/mm 3 were not as likely to progress from lower grade lesions to higher grade lesions [15]. The role of viral load, medication status, and CD4 count was not assessed, and there is one limitation in this study.…”
Section: Discussionmentioning
confidence: 99%